Anak Selangor Anak Sihat (ASAS); a public health intervention by the Selangor State Government - Rusli, Mohammad Farhan; Zainal Abidin, Muhammad 'Adil; Yaacob, Norhasniza; Mahmud, Siti Mariah (Malaysian Public Health Physicians' Association, UKM, 2023)
Summary Nutrition plays a critical role in the development of a child, ensuring a steady growth of both height and weight. Deviations of this result in obesity or stunting. Stunting has been identified to affect 7 out of 10 children in Malaysia. The Selangor state government through its public health program collaborated with the International Islamic University Malaysia to conduct a long-term intervention program known as Anak Selangor Anak Sihat (ASAS), that targets vulnerable B40 children with underweight and under height for age. Food security was also taken into account and the program was performed amongst 720 recipients spread over two cohorts for a total period of ten months. A specially crafted nutritional food basket was given monthly, and progress captured on their electronic record using the Selangkah platform.